ESTIMATION OF THE ATTENUATION OF SEISMIC WAVES BY CODA ENVELOPES IN REGIONS WITH DIFFERENT GEODYNAMIC REGIMES ON THE EXAMPLE OF THE TIEN SHAN AND THE BAIKAL RIFT - P. A. Predein; Ts. A. Tubanov (Геодинамика и тектонофизика)
Evaluation of seismic wave attenuation parameters (Q-factor and frequency parameter) in the lithosphere of the Tien Shan and the Baikal rift was carried out using coda waves of regional earthquakes. Comparison of obtained quality factor values shows that attenuation in the lithosphere of the Tien Shan is stronger than in the Baikal rift. It can be explained by a higher level of heterogeneity of medium.